RESEARCH METHODS FOR ENCODING AND DECODING CONVOLUTIONAL CODES WITH LOW DENSITY PARITY CHECK (Modern information system and technologies, 2018)
In this paper we analyze and study the main properties of block and convolutional codes with low density parity check.